"What could be a better souvenir than a lung-full of clean air?" Linguistic expressions in promoting arctic nature in Lapland destination marketing - Metsälä, Heidi (My University, 2024)
This research examines how Lapland’s arctic nature is presented as part of the destination image of Finland by tourism marketing companies. The research focuses on examining the language and, specifically, the rhetorical devices that Visit Finland and House of Lapland have chosen to use on their websites when marketing Lapland as a tourist destination. Visit Finland is a national expert unit that promotes international tourism, develops and directs Finland’s destination image marketing and also helps domestic travel companies succeed in the international tourism market. House of Lapland is the official marketing and communications house of the Lapland region. Since the material is a media text and the context is tourism marketing, the content is framed by an effort to influence the readers through positive framing. As a motivation to this research, there is an underlying question about the process of creating these positive mental images in the field of tourism marketing: how these images are created and how do they influence the potential tourists’ choices of travel destination. However, this study approaches the topic from a slightly new perspective, not only by examining the linguistic devices with which the positive image of Lapland is created, but also by studying the meaning of the created image from an ecolinguistic perspective. Firstly, this study focuses on answering two questions: what nature-related themes are highlighted in Lapland marketing, and what are the main rhetorical devices that can be found in the text. Secondly, by analyzing these linguistic devices more closely, this study aims to understand why certain rhetorical style or modes of discourse are chosen and what is their significance in creating a positive destination image. Finally, the data are further analyzed by means of ecolinguistic analysis to understand how the image, conveyed by language, could be interpreted from an environmental perspective, a non-anthropocentric view. Nine nature-related themes were identified from the research material by analyzing the text content of the websites using qualitative content analysis. The research focused on examining specifically the language used in the context of these nature-related themes. In addition, nine most used rhetorical devices were identified from the chosen text. Characteristic to the text was the abundance of positive expressions. Lapland’s unique nature and its purity were brought out visibly in the text, using several different rhetorical devices, especially targeting the international tourists. However, a skillfully created message promoting tourism and drawing on the integrity of nature can also be interpreted as problematic in terms of sustainability and the environment. Tourism as a business is understandably facing challenges when we are aiming for an environmentally sustainable future. However, the goal of preserving arctic nature is mutual, and interdisciplinary research can, at its best, stimulate constructive dialogue and even open doors to new solutions.
Keywords: framing, rhetorics, ecolinguistics, destination image, place-branding, tourism, Lapland, nature